2017
DOI: 10.1001/jamapsychiatry.2017.1682
|View full text |Cite
|
Sign up to set email alerts
|

State-Dependent Cross-Brain Information Flow in Borderline Personality Disorder

Abstract: This study provides a neural correlate for a core diagnostic and clinical feature of BPD. Results indicate that hyperscanning may deliver state-associated biomarkers for clinical social neuroscience. In addition, at least some neural deficits of BPD may be more reversible than is currently assumed for personality disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 52 publications
(78 reference statements)
3
42
0
3
Order By: Relevance
“…Related studies have revealed that interpersonal brain synchrony reflects social dysfunctions and intervention effects to some extent (80,83). Thus, it could be possible to improve the social communication and interpersonal relationships of patients with psychiatric disorders by manipulating interpersonal brain synchrony.…”
Section: Manipulation Of Inter-personal Brain Synchronymentioning
confidence: 99%
“…Related studies have revealed that interpersonal brain synchrony reflects social dysfunctions and intervention effects to some extent (80,83). Thus, it could be possible to improve the social communication and interpersonal relationships of patients with psychiatric disorders by manipulating interpersonal brain synchrony.…”
Section: Manipulation Of Inter-personal Brain Synchronymentioning
confidence: 99%
“…Within the temporo-parietal junction (TPJ), for example, brain responses become synchronized and/or contingent between interactants during economic exchanges (Jahng, Kralik, Hwang, & Jeong, 2017;Tang et al, 2016;Zhang, Liu, Pelowski, Jia, & Yu, 2017), verbal and non-verbal communication (Bilek et al, 2015(Bilek et al, , 2017Kinreich, Djalovski, Kraus, Louzoun, & Feldman, 2017;Rojiani, Zhang, Noah, & Hirsch, 2018;Wilson, Molnar-Szakacs, & Iacoboni, 2008), and cooperative joint-action tasks (Abe et al, 2019). Within the temporo-parietal junction (TPJ), for example, brain responses become synchronized and/or contingent between interactants during economic exchanges (Jahng, Kralik, Hwang, & Jeong, 2017;Tang et al, 2016;Zhang, Liu, Pelowski, Jia, & Yu, 2017), verbal and non-verbal communication (Bilek et al, 2015(Bilek et al, , 2017Kinreich, Djalovski, Kraus, Louzoun, & Feldman, 2017;Rojiani, Zhang, Noah, & Hirsch, 2018;Wilson, Molnar-Szakacs, & Iacoboni, 2008), and cooperative joint-action tasks (Abe et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, brain regions implicated in social cognitive processes feature frequently in patterns of neural coupling across various types of social interaction, presumably reflecting the mutual recruitment of mechanisms that permit the transmission and encoding of social information. Within the temporo-parietal junction (TPJ), for example, brain responses become synchronized and/or contingent between interactants during economic exchanges (Jahng, Kralik, Hwang, & Jeong, 2017;Tang et al, 2016;Zhang, Liu, Pelowski, Jia, & Yu, 2017), verbal and non-verbal communication (Bilek et al, 2015(Bilek et al, , 2017Kinreich, Djalovski, Kraus, Louzoun, & Feldman, 2017;Rojiani, Zhang, Noah, & Hirsch, 2018;Wilson, Molnar-Szakacs, & Iacoboni, 2008), and cooperative joint-action tasks (Abe et al, 2019). This is perhaps unsurprising given the putative role of the TPJ in inferring the intentional and motivational states of others (Bardi, Six, & Brass, 2017;Carlson, Koenig, & Harms, 2013;Eddy, 2016;Frith & Frith, 2006), a process that is essential for interacting successfully with others.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, both frameworks highlight the potential important theoretical and clinical implications of studying social cognition within interactive brains, especially with regards to clinical populations (Schilbach, 2016;Bilek et al, 2017). By doing so, both serve to encourage and stimulate a new line of research.…”
mentioning
confidence: 98%